2018
DOI: 10.1111/clr.13372
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants‐associated release of titanium particles: A systematic review

Abstract: Objectives The presence of titanium (Ti) particles around dental implants has been reported in the literature for decades. The prospective presence of Ti debris on soft tissues surrounding dental implants has not been systematically investigated and remains to be explored. Hence, this review aimed to evaluate the origin, presence, characteristics, and location of Ti particles in relation to dental implants. Material and methods Literature searches were conducted by two reviewers independently based on the PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 65 publications
5
116
0
4
Order By: Relevance
“…These findings corroborate the results of studies with planktonic cultures and showed a specie‐specific effect on bacteria growth in a dose‐dependent manner . Moreover, biofilm can lead to implant corrosion and even decontamination methods can affect products releasing; therefore, a synergistic effect is expected between Ti products concentration and biofilm virulence, since Ti products can increase bacteria levels and biofilm formation can enhance implant degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings corroborate the results of studies with planktonic cultures and showed a specie‐specific effect on bacteria growth in a dose‐dependent manner . Moreover, biofilm can lead to implant corrosion and even decontamination methods can affect products releasing; therefore, a synergistic effect is expected between Ti products concentration and biofilm virulence, since Ti products can increase bacteria levels and biofilm formation can enhance implant degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium (Ti) is the main dental implant material due to its excellent physical‐chemical properties and high biocompatibility with oral tissues . Nonetheless, once exposed to the oral environment, dental implants can be affected by mechanical and chemical degradation processes, such as surface corrosion and wear, which leads to the release and accumulation of Ti particles in the peri‐implant surrounding tissues . In contact with biological fluids, these particles can dissolve and generate Ti ions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the tribolayer of Ti-based implants are commonly subjected to damages by tribocorrosion phenomena since the implantation and along the lifetime service (Trino et al, 2018). Firstly, material loss can occur during the implantation when friction forces are applied to implants exposed to body fluids (Suárez-López Del Amo et al, 2018). The insertion torque, loading, and implant replacement cause friction at the bone/implant interface which may be responsible for the release of metallic wear debris causing modifications to the surface and implants geometry (Franchi et al, 2004;Fretwurst et al, 2016).…”
Section: The Relevance Of Bio-tribocorrosion In Dentistry and State Omentioning
confidence: 99%
“…These implant degradation products can trigger unfavorable biological responses such as increase in peri-implant infection and progressive bone loss . Consequently, such harmful effects influence the implant lifetime and increase the failure probability (Delgado-Ruiz and Romanos, 2018;Suárez-López Del Amo et al, 2018). For this reason, the study of the bio-tribocorrosion phenomenon has been considered a relevant topic of dental research.…”
Section: Introductionmentioning
confidence: 99%